Study and modulation of cardiac electroporation with a novel model utilizing human induced pluripotent stem cells. (14th October 2021) - Maizels, L; Heller, E; Landesberg, M; Huber, I; Arbel, G; Gepstein, A; Gepstein, L; Maor, E
Abstract: Background: Cardiac electroporation is a promising novel non-thermal ablation method, gaining significant interest with recent first-in-man data suggesting effective cardiac lesion generation with no collateral damage. Nevertheless, significant knowledge gaps exist regarding its electrophysiological consequences in cardiomyocytes, including; cell specificity, protocol optimization, irreversibility threshold, recovery time-constants, and the mechanistic nature of its cytolytic and anti-arrhythmic properties. Purpose: Establishing an innovative in-vitro model for the study of cardiac electroporation-ablation, utilizing human induced pluripotent stem cells (hiPSCs). Methods and results: Healthy-control hiPSC-derived cardiomyocytes were enzymatically dissociated and seeded as circular cell sheets (hiPSC-CCSs). Electroporation-ablation experiments were performed using a custom designed high-frequency electroporation (HF-EP) generator. Two needle-shaped electrodes were used for HF-EP delivery (Figure 1). Subsequently, detailed voltage- and Ca2+-mapping studies of the hiPSC-CCSs were conducted (Figure 2). HF-EP application resulted in the generation of electrically isolated lesions within the hiPSC-CCSs (Figure 3). Further characterization of the temporal changes and electrophysiological properties following electroporation revealed that; (1) lesions persisted over prolonged periods of time (days), indicating irreversible electroporation, (2) a temporal decrease in lesion dimensions was noted, consistent with a significant reversible electroporation component (Figures 3–5), (3) most tissue recovery had occurred within the first 15 minutes following electroporation, with little recovery beyond that time-frame, (4) increasing pulse-number augmented lesion area as well as the proportion of irreversible damage, and (5) electroporation sensitization was achieved by increasing extracellular Ca2+, indicating its crucial role in electroporation cytolysis, potentially via direct cellular toxicity and apoptosis facilitation (Figures 5–6). Finally, evaluating for HF-EP anti-arrhythmic properties, we targeted multiple rotors or focal triggered-activity generated in the hiPSC-CCSs. HF-EP application generated sustained line-blocks, isolating arrhythmogenic substrates within the hiPSC-CCSs while blocking the propagation of arrhythmic wavefronts (Figure 7). Conclusion: Our results demonstrate the ability to study cardiac electroporation utilizing hiPSC-derived cardiomyocytes, provide novel insights into its temporal and electrophysiological characteristics, facilitate electroporation protocol optimization, screen for potential electroporation sensitizers, and to study its mechanistic nature and anti-arrhythmic properties. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Division of Cardiology, and Tamman Cardiovascular Research Institute, Leviev Heart Center, Sheba Medical Center - Tel Hashomer, Ramat-Gan, Israel